Efficacy of vitamin D supplementation on depressive symptoms in older patients: a meta-analysis of randomized controlled trials - Fu, Jiamin; Zhang, Yuchi; Chen, Xiaoyu; Yu, Xing; Yan, Maoxin; Jing, Biying; Yu, Hongjuan; Li, Wenzhen; Guo, Qi (Frontiers in Medicine, 2024)
Background:The relationship between vitamin D and depression has garnered significant attention in recent years. However, the efficacy of vitamin D in ameliorating depression among specific subgroups of older patients remains controversial. This study aimed to assess the impact of vitamin D supplementation on depressive symptoms and the prevalence of depression in older adults.Additionally, the study sought to examine potential moderating factors, including differences among population subgroups and various supplementation strategies.:A systematic literature search was conducted in the databases PubMed, EMBASE, Web of Science, and the Cochrane Library up to March 2024. The RevMan 5.3 software was utilized to calculate the standardized mean difference (SMD) and to evaluate the quality of evidence using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. The objective was to determine the efficacy of vitamin D supplementation in alleviating depressive symptoms or treating depression in older adults. Results:This meta-analysis encompassed eleven studies, comprising a total of 21,561 participants. The findings did not indicate a statistically significant therapeutic benefit of vitamin D supplementation for depression in older patients [SMD: -0.10; 95% CI: (-1.19, 0.00); p = 0.05]. Subgroup analyses revealed that the efficacy of vitamin D intervention in geriatric depression correlated with several factors, including baseline serum 25(OH)D levels, the dosage of the intervention, gender, and the initial presence of depressive symptoms or a diagnosis of depression. Conclusion: The current evidence is insufficient to conclusively establish the significant efficacy of vitamin D supplementation in alleviating depressive symptoms among older patients. Consequently, additional randomized controlled trials are warranted to further validate the relationship between vitamin D supplementation and depression in the older.adults.